2017
DOI: 10.1523/jneurosci.3670-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorylation State of theDrosophilaTRP Channel Modulates the Frequency Response to Oscillating LightIn Vivo

Abstract: photoreceptors respond to oscillating light of high frequency (∼100 Hz), while the detected maximal frequency is modulated by the light rearing conditions, thus enabling high sensitivity to light and high temporal resolution. However, the molecular basis for this adaptive process is unclear. Here, we report that dephosphorylation of the light-activated transient receptor potential (TRP) ion channel at S936 is a fast, graded, light-dependent, and Ca-dependent process that is partially modulated by the rhodopsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Recently, we reported light- and RDGC-dependent dephosphorylation of TRP at Ser936 [ 8 ]. To investigate the general capacity of the rdgC ΔS , rdgC ΔSM , and rdgC ΔL flies to dephosphorylate pS936-TRP, we light and dark adapted flies for one hour and subjected fly heads to Western blot analyses ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we reported light- and RDGC-dependent dephosphorylation of TRP at Ser936 [ 8 ]. To investigate the general capacity of the rdgC ΔS , rdgC ΔSM , and rdgC ΔL flies to dephosphorylate pS936-TRP, we light and dark adapted flies for one hour and subjected fly heads to Western blot analyses ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the general capacity of the rdgC ΔS , rdgC ΔSM , and rdgC ΔL flies to dephosphorylate pS936-TRP, we light and dark adapted flies for one hour and subjected fly heads to Western blot analyses ( Fig 4A ). Using a phosphospecific antibody that was raised against a phosphorylated synthetic peptide resembling TRP phosphorylated at S936 [ 8 10 ], we found that TRP was dephosphorylated in the light and phosphorylated in the dark at S936 in rdgC ΔS , rdgC ΔSM , and rdgC ΔL fly heads like in the wild type. Thus, RDGC-M and -L ( rdgC ΔS ), RDGC-L alone ( rdgC ΔSM ), as well as RDGC-S and -M ( rdgC ΔL ) are generally capable to mediate TRP dephosphorylation at S936 in the light.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations